KAJIAN PSIKOANALISIS TERHADAP GARIS BESAR CERITA AYODHYĀ KĀṆḌA (PERSPEKTIF PENDIDIKAN AGAMA HINDU) - Pratama, I Gede Nanda Jaya; Maharani, Ni Putu Febbyana; Wijayanti, Ni Kadek Hery; Putri, Ni Kadek Ratna Chiaki (Padma Sari: Jurnal Ilmu Pendidikan, 2025)
This study examines the moral order of Hindus through psychological analysis proposed by Sigmund Freud with the aim of exemplifying moral considerations for Hindus and strengthening the implementation of moral teachings embodied in the literature of the Itihāsa Rāmāyaṇa, especially in Ayodhyā Kāṇḍa through the role of psychology. These teachings are part of the Tri Kerangka Dasar Agama Hindu, one of which is suśīla. Examined through the lens of modern science, suśīla can be considered a form of psychology because these teachings examine the attitudes and behaviors of followers based on religious morality. Suśīla teachings can be systematically studied through itihāsa texts, such as the Rāmāyaṇa, particularly the Ayodhyā Kāṇḍa chapter. This chapter represents the root of the problems in the story of Śrī Rāma's journey so followers can learn moral values from the characters' behavior. This qualitative study uses descriptive methods to describe and analyze the characters from the Ayodhyā Kāṇḍa story, including Mahārāja Daśaratha, Manthara, Dewi Keikeyi, Śrī Rāma, Sītā, Lakṣmana, and Bharata, through psychoanalytic theory. Specifically, it examines the three levels of human consciousness proposed by Sigmund Freud: The id, ego, and superego. The results of study is reveal the personality traits and dynamics of each character, setting an example for the humanity through their moral attitudes and considerations. This is particularly evident in characters who set aside their personal ego, such as Śrī Rāma, who was devoted to his father and willing to exile himself. Additionally, Bharata's humility in refusing to replace Śrī Rāma as king is driven by his superego's awareness of not taking what is not his. This psychoanalytic study imparts moral values to the community, such as resisting negative influences, remaining loyal, being devoted, and avoiding greed.